Treatment of refractory Helicobacter pylori infection: A new challenge for clinicians - Xu, XinBo; He, Cong; Zhu, Yin (Frontiers in Microbiology, 2022)
Patients who have failed two or more attempts to eradicate Helicobacter pylori are commonly referred to as refractory. Although the incidence of refractory Helicobacter pylori infection is only 10%-20%, with the increasing rate of antibiotic resistance in various regions, the treatment of refractory Helicobacter pylori infection has gradually become a difficult problem faced by clinicians. When choosing a rescue therapy, the physician must consider numerous factors. A longer treatment duration, higher doses of proton pump inhibitors (PPIs), or the use of vonoprazan may increase the efficacy of triplet or bismuth quadruple therapy. Rescue treatment based on bismuth quadruple therapy usually achieves better results. At the same time, treatment based on drug susceptibility tests or genotypic resistance is recommended where available. Of course, appropriate empiric treatment can also be selected according to local drug resistance, a patient's previous medication history and compliance. It is the best choice if it can improve the success rate of the first treatment and reduce the occurrence of refractory Helicobacter pylori infection. This review aims to summarize the articles related to refractory Helicobacter pylori in recent years and to explore a better remedial treatment plan for clinicians.